Demonstration Method in Improving Results Learning Sciences For Primary School Students - Nanda Ayu Setiawati, Yetti Rosmawati Pangaribuan, Taruli Marito Silalahi, Elida Meliana Siregar (Education Achievement: Journal of Science and Research, 2021)
This research aims to find out whether the demonstration method can improve social studies learning outcomes for elementary school students, where this type of research is qualitative research using library research methods (literature study). The data sources used in this research are secondary data sources taken from various existing literature such as books, journals and other literature related to the discussion in the thesis. The data was analyzed using qualitative data analysis which consisted of data reduction, presentation and drawing conclusions. Based on the results of discussions in research journals, it has been researched that the use of the demonstration method can improve social studies learning outcomes for elementary school students. The effective and efficient demonstration method applied by social studies teachers can have a positive influence on student learning outcomes. The stages of use in this demonstration method consist of: (1) General Steps, (2) Demonstration Steps, (3) Experimental Steps, and (4) Final Steps (Closing).